Analysis of Active Learning Strategies in Islamic Historical Culture Subject - andriani; Abbiyu Dwi Rizki; M. Fadli (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Learning Islamic Cultural History (ISH) plays an important role in shaping students' understanding of history and Islamic values. However, conventional methods that are still dominant hinder students' active involvement. This study aims to analyze relevant and effective active learning strategies in the context of ISH learning. The method used is a literature study with a qualitative descriptive approach, examining various strategies such as group discussions, role play, mind mapping, and active knowledge sharing. The results of the study indicate that active learning strategies can increase learning motivation, understanding of the material, and strengthening students' character. However, its implementation faces a number of obstacles such as limited teacher competence, facilities and infrastructure, and limited learning time. Therefore, teacher training, school management support, and the development of innovative media are needed as solutions. Active learning strategies have been shown to provide a more contextual and transformative approach to ISH learning, in line with the goals of holistic Islamic education.